The Initiatives to Improve Antenatal Care Visits By Third-Trimester Pregnant Women - Putra, Dony Setiawan Hendyca; Prasetyo, Hendro (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Low rate of pregnant women’s visit can inhibit the information health workers need to collect, subsequently posing problem in providing health assistance. This is extremely dangerous for the safety of mother and baby during childbirth. Jember district health center reported low rate of visit of third-trimester pregnant women as evidenced by an average visit of below 4 times. The aim of the study was to increase the coverage of third-trimester pregnant women’s visit based on community involvement based on factor analysis at Jember district health center. This study aims to increase the visit of trimester 3 pregnant women to public health centres. This research is an analytic research with cross sectional approach. The study involves 100 third-trimester pregnant women, chosen through random sampling. The results of this study highlight 6 independent variables that affect pregnant women visits. The most dominant influence is pregnant women’s knowledge regarding visit (p = 0.003 0.05 Exp (B) 7.523, equal to 75%). There is a significant difference between the southern and northern parts of the Jember health center with regard to knowledge, socio-cultural, and geographical location. The priority issues determined from the Focus Group Discussion process are 1) the level of knowledge; 2) social culture; and 3) geographical location. The study demonstrates that the right measures are to conduct routine counseling related to the importance of ANC visits, evaluate the presence of ANC visits and add ball pick-up services for pregnant women who do not visit ANC.